2013
DOI: 10.1186/1471-2334-13-274
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for subclinical atherosclerosis in HIV-infected patients under and over 40 years: a case–control study

Abstract: BackgroundCardiovascular diseases (CVD) are a major cause of death in people with AIDS. Factors contributing to atherosclerosis include traditional risk factors, antiretrovirals and inflammatory factors related to HIV infection. This study set out to compare risk factors associated with subclinical atherosclerosis in individuals under and over 40 years of age.MethodsCase–control study with 697 HIV/AIDS individuals without HAART or who remain on their first antiretroviral regimen. Of the total, 351 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
12
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
7
12
2
4
Order By: Relevance
“…Our final multivariate model highlighted the importance of the association between traditional CVD risk factors and cIMT. This same observation was made in a Brazilian cohort of 591 patients in whom traditional CVD risk factors predicted cIMT in multivariate analysis in those less than 40 years of age [6]. Findings of the Brazilian HIV cohort and the predominantly female HIV-infected clinical cohort in South Africa aligned with our findings and did not find an association between HIV-related factors and cIMT [7].…”
Section: Discussionsupporting
confidence: 89%
“…Our final multivariate model highlighted the importance of the association between traditional CVD risk factors and cIMT. This same observation was made in a Brazilian cohort of 591 patients in whom traditional CVD risk factors predicted cIMT in multivariate analysis in those less than 40 years of age [6]. Findings of the Brazilian HIV cohort and the predominantly female HIV-infected clinical cohort in South Africa aligned with our findings and did not find an association between HIV-related factors and cIMT [7].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies in the South indicated an association between fewer years of schooling and metabolic syndrome in men [19]. In the Northeast, an association between male sex and subclinical atherosclerosis [20] and higher velocity of pulse wave was observed, similar to the observations among HIVnegative individuals [21].…”
Section: Discussionsupporting
confidence: 76%
“…Given the restrictive inclusion criteria, we have found lower CIMT values than other studies , and only in three patients were above 0·8 mm, the usual cut‐off for the definition of ‘pathological’ CIMT. More surprising was the finding of a atherosclerotic plaque prevalence of 21% in these low‐risk patients.…”
Section: Discussioncontrasting
confidence: 71%